SECTIONAL DYNAMICS PROBLEMS AND GOVERNMENT INVOLVEMENT IN THE RESOLUTION PROCESS OF AHMADIYYA SECT IN WEST NUSA TENGGARA PROVINCE - Gaol, Alhoma R. Lumban; Primasari, Vinda Verina Kartika Dewi; Malik, Ichsan; Widodo, Pujo (Jurnal Politik Pemerintahan Dharma Praja, 2023)
Ahmadiyah is not a new religious movement in Indonesia. This paper will focus on the conflict of the Ahmadiyya Congregation in West Nusa Tenggara which shows and explores the dynamics and resolution of the conflict that occurred. This research uses descriptive qualitative approach. The data collection technique was carried out by interviewing via zoom meeting with informants by Prof. Suprapto (Deputy Chair of the West Nusa Tenggara Religious Harmony Forum). The secondary data in this study used the library research method. The data collected and processed comes from books, journal articles, and other sources that are credible and related to this research. The conclusion obtained is that the Ahmadiyya conflict in West Nusa Tenggara is one of the protracted conflicts. From 1998 to 2018 it took 20 years with an unpredictable conflict process that barely ended because the local government was not yet functioning in handling the Ahmadiyya case. The Pattern of Conflict Handling carried out by FKUB NTB in the Ahmadiyya case uses Conflict Management. However, it has not been developed thoughtfully, especially peace-building because the peacekeeping and peace-making stages have not produced results, so it isn't easy to encourage peace-building in West Nusa Tenggara In the context of conditions for the recovery of the social community in West Nusa Tenggara, it is best if the integration of the lives of the people of West Nusa Tenggara is made on the government's agenda in various related agencies. An agenda that is not only about religion but involves and involves various levels of society to build relations between communities.